ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRESTASI BELAJAR MAHASISWA DI FEB UNIVERSITAS NEGERI SURABAYA - Majesty Naftalina Harianto; Novi Marlena (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2026)
This study aims to analyze factors related to student achievement at the Faculty of Economics and Business, Universitas Negeri Semarang (UNESA). This study employed a quantitative method with factor analysis techniques, conducted using SPSS version 25 software. Data were obtained from distributing questionnaires to the study sample, namely FEB UNESA students. The results of this study, after factor rotation, yielded two factors: Learning Support Factors (Work Ethic, Family Environment, Learning Concentration, and Learning Independence), and Health Factors (Health).This research provides recommendations for future researchers, universities, students, and parents. It is particularly helpful for students, as internal factors must recognize the importance of academic achievement.